Effisiensi Penyisihan Logam Cu2+ Terhadap Adsorben Limbah Padat Tandan Kosong Sawit (TKS) Teraktivasi - Virghea Septilda Zalchie; Elvi Yenie; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The heavy metal found in industrial waste is copper (Cu). The adsorption process of the artificial Cu 2+ solution was investigated using an adsorbent made from Empty Palm Oil Bunches (EFB). EFB is one of the largest solid wastes produced from agricultural activities which contain lignocellulose. Lignocellulose is the main component of EFB which has the ability to adsorb heavy metals because it contains active groups such as –OH and COOH. This study aims to calculate the efficiency of metal ion Cu2+ on EFB adsorbent, with adsorbent mass variation 0.5; 2; 3.5; 5 and 6.5 grams. the best efficiency results were obtained, namely the adsorbent mass of 6.5 grams, which was 79.33%.Keywords: Adsorption, , Cu2+, Palm Empty Fruit Bunches (EFB).